Four-armed Agni depicted with a Shruka and a Pustaka - Temples of India Project Team (Jio Institute, 2024)
The four-armed Agni is depicted with a shruka (sacrificial ladle) and a pustaka (book) in his upper hands. His lower right-hand makes a varada hasta (boon-giving gesture), while his lower left hand holds a kamandalu (water pot). He is adorned with a jatamukuta (crown of matted hair), a moustache, and a long, intricately knotted beard, He is bejewelled and accompanied by his mount, the ram.